If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = -2g Solving 4 = -2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '2g' to each side of the equation. 4 + 2g = -2g + 2g Combine like terms: -2g + 2g = 0 4 + 2g = 0 Add '-4' to each side of the equation. 4 + -4 + 2g = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2g = 0 + -4 2g = 0 + -4 Combine like terms: 0 + -4 = -4 2g = -4 Divide each side by '2'. g = -2 Simplifying g = -2
| .4n=12 | | -x/24=4 | | 2c+(3c+-4)=5c+-4 | | 6=r-7 | | y=9x+3x | | Z-5-13= | | X+(-8)=-16 | | 3y+15=36 | | 2c+(3c+-4)=4c+-4 | | -4(n+2)=-5n | | (8x^4y^2/3z^3)*(9xy^2z^6/4y^4) | | 1.21=11(0.5+0.4x)whatisx | | -33/4x=-60 | | 12*x=132 | | 8+4v+8v+5=1+8v | | (8x^4y^2/3z^3)*(9xy^2z^6) | | 4a+3b+8-2a-3b= | | 3x-54=44+10x | | 5x+4-x=4+3x-4 | | 3(x-6)=4x-x+2 | | 7x+9=x-3y | | 2x+(2b-1)y=4 | | 23-48x=82x+56 | | -4-3(x-5)=12x+2(x-3) | | -44+x=20 | | Hb-3v=0 | | 5(x-5)=5x+12 | | H=3v/b | | 2=(x-2.1)/1.3 | | r/3=-9 | | 6-8+3x+2x=2x-2+3x | | 89=65+n |